সমকালীন রাজনীতি প্রসঙ্গ ও অন্যান্য - ইবরাহিম, সৈয়দ মুহাম্মদ 1949- (ঢাকা : অনন্যা প্রকাশনী, 2015)
Articles on contemporary politics of Bangladesh.
In Bengali.
Keywords: Bangladesh -- Politics and government -- 1971-